Estimation of employed persons in the case of sample rotation - Chadyšas , Viktoras; Krapavickaitė, Danutė (Lietuvos matematikos rinkinys, 2008)
The aim of the paper – to investigate effectiveness of the ratio estimator in the labour force survey in the case of the simple random sampling with rotation. For each quarter of the year one fourth of the previousquarter sample is changed with the new one, and three fourth’s are remaining the same. After simplification of the sampling design the estimator using auxiliary information and its approximate variance is constructed. The accuracy of the estimator obtained is studied by modelling with the real data.
Keywords: labour force survey; two phase sampling design; ratio estimator